Investigation of Solid Formation Enthalpy and Molecular Mechanics Energies of Amino Acids via Force Field Approach - Songur, Levent; Orhan, Oguzhan; Ozgen, Soner (My University, 2023)
Amino acids which are organic compounds directly affect gene expression and control of the function of proteins. Their enthalpy values and molecular mechanical energies of them profoundly influence the protein folding mechanism. Molecular modeling simulations are one of the methods used to obtain their properties. In this study, the enthalpy values and molecular mechanics parameters of 17 amino acids have been investigated by the classical molecular dynamics simulation based on the force-field potential approach. Enthalpy values obtained from the simulation study for ALA, ASN, ASP, CYS, LYS, and PHE are in good agreement with the experimental data. In addition, molecular mechanics parameters such as Coulomb, bond, angle, dihedral, and Van der Waals have been calculated for all amino acids. It is represented that the Coulomb energy is quite low compared to the rest of the molecular mechanical energies. Their enthalpy and molecular energy values are crucial for molecular biology studies such as electronic interaction in protein-lipid modification, ligand binding to the cell surface, and correct protein localization.
Keywords: Amino Acids; Molecular Dynamics; Solid Formation Enthalpy; Molecular Mechanics Energies